2008
DOI: 10.1111/j.1365-2710.2007.00891.x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and predictors of potential drug–drug interactions in Regione Emilia-Romagna, Italy

Abstract: A substantial number of clinically important potential DDIs were identified, particularly among warfarin users. Awareness of the most prevalent potential DDIs can help practitioners prevent concomitant use of these dangerous medication combinations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
79
2
16

Year Published

2008
2008
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 88 publications
(106 citation statements)
references
References 73 publications
9
79
2
16
Order By: Relevance
“…In the study conducted in Brazilian primary public health system the most commonly drug pairs were digoxin and furosemide/hydrohlorothiazide, captopril/losartan and spironolactone, and acidum acetylsalicylicum and ticlopidine [22]. In ambulatory medical care practices in the US, Aparasu et al identified that warfarin included in the three most commonly DDIs pairs [17], similar to the results of study was conducted in Italian outpatients [31].…”
Section: Icd-10-cm Code M00-m99supporting
confidence: 61%
See 3 more Smart Citations
“…In the study conducted in Brazilian primary public health system the most commonly drug pairs were digoxin and furosemide/hydrohlorothiazide, captopril/losartan and spironolactone, and acidum acetylsalicylicum and ticlopidine [22]. In ambulatory medical care practices in the US, Aparasu et al identified that warfarin included in the three most commonly DDIs pairs [17], similar to the results of study was conducted in Italian outpatients [31].…”
Section: Icd-10-cm Code M00-m99supporting
confidence: 61%
“…These findings could be attributed to the increased complexity of drug therapy regimens found in older, which resulted in a higher prevalence of potential DDIs. However, in the study conducted by Gagne et al in Italy, using subjects aged 50-64 years as a referent group, the odds of exposure to a potential DDIs was higher in older patients, however odds of exposure for the oldest (aged ≥ 85 years, OR=2.02 (95% CI of 1.66-2.46)) was lower than for those aged of 65-74 years [31]. Some studies failed to document a positive association between years and exposure to potential DDIs [45,46].…”
Section: Patient Characteristic Predictorsmentioning
confidence: 78%
See 2 more Smart Citations
“…Além dos eventos adversos, a varfarina está entre os fármacos com maior número de interações medicamentosas (JACOBS, 2008;BONATE et al, 2016), a maioria com importância clínica (GAGNE et al, 2008). Kotirum et al (2007) verificaram que 83,6% dos pacientes usuários de varfarina apresentam, pelo menos, uma interação medicamentosa com este medicamento.…”
Section: Introductionunclassified